Telaah kritis terhadap masyarakat madani (civil society) - Suharno Suharno (Jurnal Civics: Media Kajian Kewarganegaraan, 2007)
Discourse about civil society is almost being a main topic at any conversations beside topics of httman rights, democracy, reforms and globalization. Civil society is a kind of society which are open, plttralzstic, decentralized with a massive partiapation on politic activities, honest,fair, selfhelp, harmony, gttarantee the freedom of faith, speaking, making or involving in a union, expressing themselves, of the property rights and respect btanan rights. The realization needs process and time and commitment from all citizen to riform themselves totaly and always consistent and wise to react on deniable conflict.